Pengungkapan Corporate Social Responsibility dan Profitabilitas terhadap Agresivitas Pajak dengan pemoderasi Intellectual Capital - Manda Ari Maylanti; Sugiyanto Sugiyanto (STIE-JIC, 2023)
The study investigated the relationship between corporate social responsibility disclosure, profitability, and tax aggressiveness in an Indonesian coal mining sub-sector. The study utilized quantitative research methods with purposive sampling to select a sample of ten coal mining companies listed on the Indonesia Stock Exchange from 2016 to 2021. The data were analyzed using panel data regression. The study revealed a positive relationship between corporate social responsibility disclosure, profitability, and tax aggressiveness. In other words, companies that disclose more information on their social responsibility and are more profitable are likelier to engage in tax aggressiveness. This finding suggests that firms use corporate social responsibility to improve their image and reputation while also engaging in tax avoidance practices. Moreover, the study found that effective intellectual capital management can strengthen the relationship between corporate social responsibility disclosure, profitability, and tax aggressiveness. This result implies that companies better equipped to manage their intellectual capital will likely leverage their corporate social responsibility initiatives to achieve financial and reputational benefits. Overall, the study contributes to the literature on corporate social responsibility and tax aggressiveness and highlights the importance of intellectual capital in the relationship between these two constructs. Companies and policymakers can use the findings to develop strategies for balancing corporate social responsibility and tax planning practices.